1977
DOI: 10.1161/01.cir.56.2.278
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic measurement of right ventricular wall thickness. A new application of subxiphoid echocardiography.

Abstract: and their relation to concurrent aging changes. (P < 0.001) in the combined group (0.62 ± 0.18 cm), the right ventricular (RV) pressure overload group (0.60 ± 0.13 cm) and the RV volume overload group (0.53 ± 0.11 cm). Thirty-two patients underwent diagnostic right heart catheterization which revealed a good correlation between the RVWT measured echocardiographically and the right ventricular peak systolic pressure (r = 0.84).Subxiphoid echocardiography was considered to be useful in diagnosing right ventricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
3

Year Published

1981
1981
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(32 citation statements)
references
References 19 publications
1
28
0
3
Order By: Relevance
“…Quantification of RV hypertrophy (RVH) is also difficult to measure and is largely a qualitative assessment. [42][43][44] Two-dimensional echocardiography is recommended to assess RA enlargement 45 and the presence and severity of pericardial effusion. 46 RA size as a surrogate for RA pressure and pericardial effusions predict survival or the need for by guest on http://circ.ahajournals.org/ Downloaded from transplantation in adults with PH.…”
Section: Estimates Of Ventricular Functionmentioning
confidence: 99%
“…Quantification of RV hypertrophy (RVH) is also difficult to measure and is largely a qualitative assessment. [42][43][44] Two-dimensional echocardiography is recommended to assess RA enlargement 45 and the presence and severity of pericardial effusion. 46 RA size as a surrogate for RA pressure and pericardial effusions predict survival or the need for by guest on http://circ.ahajournals.org/ Downloaded from transplantation in adults with PH.…”
Section: Estimates Of Ventricular Functionmentioning
confidence: 99%
“…Interventricular septal thickness and movement were also studied in all pa tients. However, we tried to obtain a good picture of the right ventricular anterior wall (RVAW): all pa tients were submitted to a recording in a supine posi tion placing the transducer inferiorly and laterally to the xiphoid appendix [12], In 34 patients out of 42 we were able to visualize the thickness of RVAW (RVAWT), which was measured at the start of the Q wave. Right ventricular diameter could be visualized (and thus RVI could be calculated) in 29 patients out of 42.…”
Section: Methodsmentioning
confidence: 99%
“…In the last few years the échocar diographie method has been suggested as a noninvasive estimation of pulmonary artery pressure in COLD [4] and in other pathology [9,16,17]: Kasper et al [9] stud ied the diameter of right pulmonary ar tery, Silverman et al [16] studied the ratio of the right ventricular pre-ejection period to the right ventricular ejection time, and Boyd et al [4] studied the time interval be tween the closure of the tricuspid valve and the maximal opening of the pulmon ary valve. Nevertheless, Matsukubo et al [12], Prakash et al [13] and Louridas et al [Il] have shown that right ventricular hy pertrophy and dilatation may be recog nized by the subxiphoid and left sternal approach to the right ventricle, yet écho cardiographie studies of the right ventri cle, together with hemodynamics of the lesser circulation, have never been carried out in COLD.…”
Section: Introductionmentioning
confidence: 99%
“…A espessura da parede VD é uma medida útil para a avaliação de hipertrofia de VD, geralmente como resultado de sobrecarga da PSVD. [16][17][18] Aumento da espessura do VD pode ser encontrado em pacientes com miocardiopatia hipertrófica e infiltrativa, assim como em pacientes com hipertrofia significativa do VE, mesmo na ausência de HP. 19 A espessura da parede livre do VD pode ser medida ao final da diástole pelo modo M ou pela ecocardiografia 2D a partir da janela subcostal, preferencialmente ao nível da ponta da cúspide anterior da valva tricúspide ou nas janelas paraesternais esquerdas.…”
Section: B Ventrículo Direitounclassified
“…19 A espessura da parede livre do VD pode ser medida ao final da diástole pelo modo M ou pela ecocardiografia 2D a partir da janela subcostal, preferencialmente ao nível da ponta da cúspide anterior da valva tricúspide ou nas janelas paraesternais esquerdas. 4,16 A partir da janela subcostal, é possível o alinhamento do feixe de ultrassom perperdicular à parede livre de VD. A exclusão das trabeculações do VD e dos músculos papilares da borda endocárdica do VD são críticas para a medida acurada da espessura da parede VD.…”
Section: B Ventrículo Direitounclassified